Strengthening of Square Configuration Micropiles for Shallow Foundations Under Eccentric Loading on Soft Clay - Ahmad Dzikrullah Akbar; Yudhi Lastiasih (Jurnal Ragam Pengabdian, 2026)
Abstract:                       Soft clay soils pose a risk of sudden shear failure in shallow foundations, particularly under eccentric loading. This study examines the effectiveness of foundation reinforcement using square configuration micropiles to enhance bearing capacity under eccentric conditions. Numerical analysis was conducted using 2D plane strain modeling with the finite element method (Plaxis 2D) and the Soft Soil material model for cohesive clay with a shear strength of 14.85 kPa. Eccentricity variations (e/B = 0–0.25) were applied to evaluate changes in bearing capacity before and after reinforcement. The simulation results indicate that eccentricity reduces the foundation's bearing capacity by up to 44% compared to concentric loading. The installation of square micropiles increased the average bearing capacity by 51.47% compared to the unreinforced condition. Regression analysis resulted in an empirical equation for the increase in bearing capacity (Rq) influenced by the micropile's frictional resistance (Qs) and the composite system stiffness (Pmaks). These findings provide a practical design basis for shallow foundations in soft soils subjected to eccentric loads, thus enhancing the stability and safety of the structure